Administration of 2.5 mg of estradiol followed by 1,500 mg of progesterone to anovulatory mares promote similar uterine morphology, hormone concentrations and molecular dynamics to those observed in cyclic mares - Silva, E. S.M. [UNESP]; Ignácio, F. S. [UNESP]; Fritsch, S. C. [UNESP]; Zanoni, D. S. [UNESP]; Pantoja, J. C.F. [UNESP]; Oliveira-Filho, J. P. [UNESP]; Meira, C. [UNESP] (Elsevier, 2017)
To test the hypothesis that the administration of 2.5 mg of estradiol benzoate (EB) followed by 1500 mg of long acting progesterone (LA P4) causes similar uterine changes and molecular dynamics in anovulatory mares to those observed in cyclic ones, we evaluated the changes of estrogen (ERα and ERβ) and progesterone receptors (PR) in anestrous, transitional and cyclic mares by RT-qPCR and immunohistochemistry. In addition, we evaluated uterine edema, tonus and estrogens and progesterone plasma profile. Endometrial biopsies were taken from anestrous and transitional mares immediately before EB injection, 48 h after EB administration and five days after LA P4 was given. In cyclic mares, biopsies were collected at estrus and at five days after ovulation. Similar estrogen peaks were achieved after the injection of the single EB dose between treated and cyclic groups, as well as maximum uterine edema. Uterine tone was increased to diestrus levels after administration of 1500 mg of LA P4. Changes in relative abundance of transcripts for PR, ERα and ERβ when progesterone stimulated endometrium was compared to estrogen stimulated endometrium were similar between cyclic and non-cyclic treated mares. However, apparent decreased PR in the endometrial glandular epithelium was not observed in non-cyclic mares five days after LA P4 administration as observed at five days after ovulation in cyclic mares. The protocol produced similar endometrial edema, uterine tonus and changes in relative abundance of PR, ERα and ERβ transcripts to those observed in cyclic mares during late estrus and early diestrus, as well as similar estradiol and estrogen conjugate plasma concentrations.
Keywords: Embryo transfer; Equine; Hormonal protocols; Steroid receptors